PENINGKATAN PERILAKU KELUARGA SADAR GIZI DI KELURAHAN DURI SELATAN, KECAMATAN TAMBORA, JAKARTA BARAT - Iskari Ngadiarti; Syarifah Miftahul El J.T1; Ma’muratun; Yusmaniar; Ruth Elenora1; Kusrini Wulandari; Rosita Gusfourni; Elsye Rahmaty; SUGENG WIYONO (AMMA : Jurnal Pengabdian Masyarakat, 2022)
. Duri Selatan Village is one of the villages that has relative low health data compared to other villages in Tambora sub-district. The largest disease data in this region are ARI (34,6%), Hypertension (26,5%), Gastritis, Diabetes Militus, Myalgia, Dermatitis and Diarrhea. While, 6.047 children under five (18,8%) suffered from malnutrition and diarrhea and 16.8% experienced stunting.  The aim of training is to create a realization of healthy RW in an attempt to increase Nutrition Conscious Family through interprofessional collaboration in Duri Selatan Village, Tambora Sub-District, West Jakarta. 44,0% Nutrition Conscious Family training participants were aged 39-40 years, primary and secondary education levels were respectively 50,0% and 97,0% as housewives. Behavioral component of Nutrition Conscious Family training participants was 34,0% not used to conduct weighing weight regularly, not exclusively breastfeeding by 25,9%, consuming non-diverse foods by 4,0%, not using iodized salt by 6,0%, when pregnant did not take blood-added tablets (TTD) by 16,0%, Women of childbearing age did not take blood-added tablets (TTD) by 40,0%, postpartum mothers did not consume high-doses of Vitamin A capsules by 50,0% and children under five were not given high doses of Vitamin A capsules by 66,0%. There is an increase 6,3 points of Nutrition Conscious Family knowledge after the training was conducted. Nutrition Conscious Family behavior is successively 75,0% Nutrition Conscious Family behavior is less 75,0%, by 16,0% Nutrition Conscious Family behaviour is between 75,0-99,0%, and by 9,0% Nutrition Conscious Family behavior is full 100,0%.